Pengembangan Buku Panduan Budaya Kerja Berbasis Religius di Sekolah Menengah Kejuruan - Muhamadi, Arif; Dahlan, Bakhrun; Susatya, Edhy; Pamilih, Indra Jamal; Sunarso; Raharjo, Slamet; Hasanah, Noviatun (Indo-MathEdu Intellectuals Journal, 2026)
Abstract. SMK graduates face challenges in work culture alignment. 5R implementation at SMK Muhammadiyah 2 Jatinom is not yet internalized sustainably. This study aims to develop a religious-based 5R work culture guidebook. The method uses Research and Development (R&D) with the ADDIE model involving 85 teachers and employees, and validation by ten experts. Results show current 5R conditions are at the habituation stage but depend on external supervision. Strategic religious values like amanah and discipline are integrated into 5R elements. The product was declared feasible in the "Good" category (score 3.60) by experts. Field trials showed the product was practical (3.48), effective (3.48), and well-accepted (3.56) by 90.5% of users. Religious value integration changed 5R perception from administrative burden to worship, increasing intrinsic motivation. It is concluded that the guidebook is feasible for adoption as a permanent institutional guide to build sustainable work culture through balancing technical, pedagogical, and spiritual dimensions. Keywords: Work culture, 5R, Religious values, ADDIE, SMK Abstrak. Lulusan SMK menghadapi tantangan kesenjangan budaya kerja industri. Penerapan 5R di SMK Muhammadiyah 2 Jatinom belum terinternalisasi secara berkelanjutan. Penelitian ini bertujuan mengembangkan buku panduan budaya kerja 5R berbasis nilai religius. Metode menggunakan Research and Development (R&D) dengan model ADDIE melibatkan 85 guru dan karyawan, serta validasi sepuluh ahli. Hasil menunjukkan kondisi 5R saat ini berada pada tahap pembiasaan namun bergantung pada pengawasan eksternal. Nilai religius strategis seperti amanah dan disiplin diintegrasikan ke dalam elemen 5R. Produk dinyatakan layak kategori "Baik" (skor 3,60) oleh ahli. Uji lapangan menunjukkan produk praktis (3,48), efektif (3,48), dan diterima baik (3,56) oleh 90,5% pengguna. Integrasi nilai religius mengubah persepsi 5R dari beban administratif menjadi ibadah, meningkatkan motivasi intrinsik. Disimpulkan buku panduan layak diadopsi sebagai panduan institusional permanen untuk membangun budaya kerja berkelanjutan melalui keseimbangan dimensi teknis, pedagogis, dan spiritual. Kata Kunci: Budaya kerja, 5R, Nilai religius, ADDIE, SMK